Clinical 'Pearls' of maternal critical care: part I. Issue 3 (June 2016) - Patil, Vinod; Wong, Michael; Wijayatilake, Dhuleep S.
Abstract : Purpose of review: This review outlines the challenges in looking after pregnant women with thromboembolism and sepsis who either become or are at risk of becoming critically ill during pregnancy. Recent findings: The Pregnancy Mortality Surveillance systems in both the USA and UK record the most common causes of maternal death as thromboembolism and sepsis. Both of these conditions have improved outcomes with timely maternal critical care provided by a multidisciplinary team. Summary: In this review, we discuss the pathophysiology, diagnosis, and management of thromboembolism and sepsis, two very important conditions with high mortality requiring admission to intensive care.